An Integrated Mobile Identity Authentication Model - Abwao, Donatus Omondi (JOOUST, 2023)
Personal identity theft is an illegal act that involves a perpetrator possessing an identity of a victim without their knowledge nor consent and in most cases for monetary gain or criminal fraudulent activities that the culprit hides in. Mobile identity has theft related cases where an identity theft criminal acquires a target person’s identity for his or her own advantage. Mobile identity theft still exists with many studies reporting despite increase of security measures from the industry and other public awareness on personal mobile security. This study identified mobile identity theft as a problem in the mobile phone industry data security, orchestrated by offenders who leverage on vulnerabilities at subscriber identity module (SIM) registration and replacement processes. The study finds that vulnerability at the subscriber identity module is a type of authentication process and besides the degree of problem isolation, categorizes the authentication clusters in their operational context. The study then proposed, developed and simulated the integrated authentication model to mitigate the problem by confirming that addition of an integrated population registration records would contribute to mitigate the problem. The study used model development methodology. The developed model was tested through a simulation process using data generated from constructs of the developed model passed through a formula that determines strength of authentication score and it was observed that maximum authentication was achieved at a maximum level of authentication for all parameters. The study also noted that the introduction of the IPRS, P enhanced the model and prevents any weakening of authentication. The study therefore confirmed that maximum level of stable authentication could be achieved by introducing an integrated population records to the already existing authentication model with maximum level of security. The study also pointed out that the security level of “user knows” and “user is” share similar authentication behavior implying that where static biometric authentication was used, knowledge-based authentication may not make much significance.
Keywords: Integrated Mobile Identity; Authentication Model